(untitled) (Scientific journal of the Fergana State University, 2023)
Polysaccharides are polymers with a wide spectrum of biological activity. They contribute to detoxification of the body, remove toxic substances, cholesterol, heavy metals, radionuclide from the body, and also repair damaged cells, do not allow the formation of free radicals, restores the immune system. In medicine, based on polysaccharides, biological active additives such as rheopolyglucin, polyglucin, heparin, mucaltin and others have been created.